CFD simulation and validation of flow in small arteries to enable further drug delivery studies (2020)
ABSTRACT : Treatments based on nanocarriers such as nanoparticles have emerged as alternatives to overcome common limitations and side effects caused by traditional treatments against cancer and neurological diseases. The main attribute of nanoparticles stems from the fact that they can transport pharmacological agents in a guided manner. This allows drugs to selectively target diseased rather than healthy tissues. This work was aimed at modeling and simulating fluid flow inside small arteries and experimentally validating the model through quantitative measurements of pressure and flow rates. The validity of the model was evaluated in the light of different indexes of percentage agreement between simulated and measured values. The model was previously verified via mesh convergence analysis and qualitative observations of velocity profile. Our findings provide a robust basis for studying nanoparticle transport in arteries as the developed platform enables their releasing and remote manipulation both in silico and in vitro.